Vibration control of a seismically-excited flexible structure using the filtered-E LMS algorithm - Rabuya, I.A.; Sison, L.G.; Burgos, O.T. (TENCON 2004 : 2004 IEEE Region 10 Conference : proceedings : analog and digital techniques in electrical engineering : 21-24 November, 2004, Chiang Mai, Thailand, 2004)
Adaptive feedforward control using the filtered-E LMS algorithm is used to control the vibrations of a flexible structure. The structure is seismically-excited using a scaled El Centro earthquake record. Ground and top floor accelerations are sensed using accelerometers, and an active mass damper mounted on top of the structure is used to cancel out the vibrations. Simulations are used to train the adaptive filter on the dynamics of the structure. Experimental results show that the top floor peak absolute acceleration of the flexible structure is reduced by 56%.